Disease-related malnutrition in children and role of oral nutrition supplement: - - Sidiartha, I Gusti Lanang; Pratiwi, I Gusti Ayu Putu Eka; Subanada, Ida Bagus (Paediatrica Indonesiana, 2023)
Background Disease-related malnutrition (DRM) is a common complication in chronic diseases. An oral nutrition supplement (ONS) is a formula with high energy density which is commonly used to treat malnutrition. Objective To identify the prevalence of DRM in children with chronic disease and evaluate the benefits of ONS. Methods A retrospective study was conducted at Prof. IGNG Ngoerah Hospital, Denpasar, Bali. Data were collected from medical records of patients who were admitted from January to December 2021. Inclusion criteria were patients aged 1-18 years with chronic diseases. Patients with organomegaly, edema, and incomplete medical record data were excluded. Disease-related malnutrition was defined as weight-for-height (for < 5 years of age) or BMI-for-age < -2SD (for > 5 years of age), according to the WHO growth charts. Subjects who received ONS for more than 80% of total energy during hospitalization were classified as part of the ONS group and the rest as standard group. Several variables between ONS and standard group were analyzed and considered significant if P value < 0.05. Results Of 313 subjects with chronic disease, 139 (44.4%) were diagnosed with DRM. Among of 139 subjects with DRM, a total of 64 subjects were analyzed in the ONS and standard feeding groups. No significant difference was found between groups with regards to age, gender, weight, height, white blood cell count, and lymphocyte cell count. Subjects with severe malnutrition significantly more classified as an ONS group than subjects with moderate malnutrition (P=0.001). Mean length of hospital stay was significantly shorter in the ONS group [11.8 (SD 6.7) days] than in the standard group [16.1 (SD 6.6) days]; (P=0.012). Conclusion Malnutrition related to chronic disease in children is prevalent. Use of ONS is associated with a shorter length of hospital stay. Thus, routine nutritional status assessment to identify malnutrition in children with chronic disease is needed to treat with ONS in order to improve prognoses.